Autonomic Cardiovascular Control and Executive Function in Chronic Hypotension. Issue 3 (12th December 2016) - Duschek, Stefan; Hoffmann, Alexandra; Reyes del Paso, Gustavo A.; Ettinger, Ulrich
Abstract: Background: Chronic low blood pressure (hypotension) is characterized by complaints such as fatigue, reduced drive, dizziness, and cold limbs. Additionally, deficits in attention and memory have been observed. Autonomic dysregulation is considered to be involved in the origin of this condition. Purpose: The study explored autonomic cardiovascular control in the context of higher cognitive processing (executive function) in hypotension. Methods: Hemodynamic recordings were performed in 40 hypotensive and 40 normotensive participants during execution of four classical executive function tasks (number-letter task, n-back task, continuous performance test, and flanker task). Parameters of cardiac sympathetic control, i.e., stroke volume, cardiac output, pre-ejection period, total peripheral resistance, and parasympathetic control, i.e., respiratory sinus arrhythmia and baroreflex sensitivity, were obtained. Results: The hypotensive group exhibited lower stroke volume and cardiac output, as well as higher pre-ejection period and baroreflex sensitivity during task execution. Increased error rates in hypotensive individuals were observed in the n-back and flanker tasks. In the total sample, there were positive correlations of error rates with pre-ejection period, baroreflex sensitivity and respiratory sinus arrhythmia, and negative correlations with cardiac output. Conclusions: Group differences in stroke volume, cardiac output, and pre-ejection period suggest diminished beta-adrenergic myocardial drive during executive function processing in hypotension, in addition to increased baroreflex function. Although further research is warranted to quantify the extent of executive function impairment in hypotension, the results from correlation analysis add evidence to the notion that higher sympathetic inotropic influences and reduced parasympathetic cardiac influences are accompanied by better cognitive performance.